SELECTION OF SUMBA ONGOLE (SO) CATTLE BASED ON BREEDING VALUE AND PERFORMANCE TEST - Said, S.; Agung, P. P.; Putra, W. P. B.; Anwar, S.; Wulandari, A. S.; Sudiro, A. (Diponegoro University, 2016)
Selection of livestock was purposed to increase productivity. A performance test was conducted using 25 males and 25 females of Sumba Ongole (SO) cattle. The performance test were conducted in three periods (2014, 2015 and 2016) for about 535 days. Descriptive statistics ws used to analyze data of body weight. Cattle with age between 300 to 600 days were used for evaluation. Result showed that heritability value of yearling weight (YW365) was 0.77+0.68 as a high category. The highest breeding value of YW365 were 66.05 kg (male) and 41.89 kg (female). The average of corrected final weight (CFW) weight were 172.55+34.22 kg (male) and 159.80+37.73 kg (female). The performance test in this study obtained six A class (1 bull and 5 cows) based on the standard minimum of body measurements for SO cattle.